Palliative cancer patients pain reduction methods during opioid epidemic era - Sobańska, Natalia; Bednarz, Katarzyna; Banaś, Patryk; Banasiak, Aleksandra Paulina; Teichman, Rafał; Kasprowicz, Jakub; Pierzchała, Jakub Rafał; Abram, Kamila; Adamus, Justyna; Hyjek, Michał (Journal of Education, Health and Sport, 2022)
Introduction: Opioids are the most commonly used medication in palliative cancer pain treatment due to their proven effectiveness. However, modern anti-pain treatment concentrates not only on analgesics, but simultaneously on the detection of conditions affecting and intensifying pain sensation. Many studies have shown potential of other, non-opioidal palliative cancer pain treatment with additional positive effect on patient’s general quality of life. Aim of the study: The purpose of our review is to introduce the issue of the use of opioids and draw attention to other non-opioidal pain reduction methods as well as to indicate directions for further potential researches. Methods and materials: We have reviewed the literature available in the PubMed, Google Scholar, Science Direct database using the keywords: „cancer patients and opioids”; „pain and cancer”; „chronic pain”; „palliative cancer”. We excluded abstracts, comments, and non–English language articles. Results: The methods outlined in this review will not affect pain reduction to the same extent as opioids, but they offer a chance to reduce it to a level that allows patients to maintain a normal life. In the light of opioid epidemic era literature shows new approaches to treating pain such as analgesics, including antidepressants, anticonvulsants, Vitamins, cannabis and nonpharmacological methods and showing their potential for wider use in palliative cancer patients treatment. Conclusion: Besides opioids, there are many factors that affect pain reduction, however, their analgesic potential require additional studies on larger groups of patients.